Familiar form of ASD with Mitral Stenosis – An Uncommon Presentation of Lutembacher’s Syndrome - Anwar, AFM Azim; Mumu, Sanjida Anjum; Khondokar, Md Noornabi; Islam, Md Tafijul; Islam, Md Azharul; Mahmood, Manzoor; Khaled, Md Fakhrul Islam (University Heart Journal, 2024)
Lutembacher’s syndrome refers to combination of congenital Atrial Septal Defect with acquired mitral stenosis. Lutembacher’s syndrome is a vety rare disease and in the past, it has been either over diagnosed or misdiagnosed. Here, we will discuss the case of a lady who presented with chief complaints of palpitation and dyspnea and after detailed examination and investigations; she was diagnosed as a case of “Lutembacher’s syndrome”. University Heart Journal 2023; 19(2): 66-70